Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1155/2017/1759469
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Metal Nanoparticle Arrays in the ZrO2(Y), HfO2(Y), and GeOx Films by Magnetron Sputtering

Abstract: The single sheet arrays of Au nanoparticles (NPs) embedded into the ZrO 2 (Y), HfO 2 (Y), and GeO x ( ≈ 2) films have been fabricated by the alternating deposition of the nanometer-thick dielectric and metal films using Magnetron Sputtering followed by annealing. The structure and optical properties of the NP arrays have been studied, subject to the fabrication technology parameters. The possibility of fabricating dense single sheet Au NP arrays in the matrices listed above with controlled NP sizes (within 1 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
0
3
0
2
Order By: Relevance
“…The ZrO 2 (Y) film with d 1 ≈ 5 nm was deposited onto the ITO layer by radio-frequency (RF) magnetron sputtering of a pressed powder ZrO To form the Au NPs, the stack was annealed at ≈450 • C in Ar ambient for ≈2 min. Earlier, the round Au NPs with R = 1-2 nm arranged in single sheet arrays inside the ZrO 2 (Y) films were shown to form after annealing of the ZrO 2 (Y)/Au/ZrO 2 (Y) stacks fabricated in the same regime [19,20].…”
Section: Methodsmentioning
confidence: 99%
“…The ZrO 2 (Y) film with d 1 ≈ 5 nm was deposited onto the ITO layer by radio-frequency (RF) magnetron sputtering of a pressed powder ZrO To form the Au NPs, the stack was annealed at ≈450 • C in Ar ambient for ≈2 min. Earlier, the round Au NPs with R = 1-2 nm arranged in single sheet arrays inside the ZrO 2 (Y) films were shown to form after annealing of the ZrO 2 (Y)/Au/ZrO 2 (Y) stacks fabricated in the same regime [19,20].…”
Section: Methodsmentioning
confidence: 99%
“…The stack was annealed at 450 C during 2 min. Earlier, we found that the Au film transforms into a planar array of spherical Au NPs with the diameters ranging from 2 to 3 nm after annealing in the regime specified above [16]. Afterwards, the round Au top electrodes of 0.5 mm in diameter and 40 nm in thickness with 40-nm thick Ta sublayers were deposited through a shadow mask.…”
Section: Methodsmentioning
confidence: 99%
“…After deposition the sandwich structures were annealed in air at 450 • C for 2 min. A more detailed procedure for the formation of ZrO 2 (Y) films with Au NP arrays, as well as the results of studies of their structure and optical properties are given in [7,8]. According to the data of high-resolution transmission electron microscopy on transverse sections the Au island film ∼ 1 nm thick ruptures upon annealing under the indicated conditions and coagulates into NPs with a diameter of D = 2−3 nm, located practically in one plane at fixed distances from the film surface and the film substrate interface (which, in turn, are determined by the thicknesses of the coating and underlying oxide layers).…”
Section: Experimental Partmentioning
confidence: 99%